Evaluation of Iterative Denoising 3-Dimensional T2-Weighted Turbo Spin Echo for the Diagnosis of Deep Infiltrating Endometriosis. Issue 10 (October 2021) - Florin, Marie; Vaussy, Alexis; Macron, Laurent; Bazot, Marc; Stemmer, Alto; Pinar, Ugo; Jarboui, Lamia
Abstract : Objectives: The primary end point of this study was to evaluate the image quality and reliability of a highly accelerated 3-dimensional T2 turbo spin echo (3D-T2-TSE) sequence with prototype iterative denoising (ID) reconstruction compared with conventional 2D T2 sequences for the diagnosis of deep infiltrating endometriosis (DIE). The secondary end point was to demonstrate the 3D-T2-TSE sequence image quality improvement using ID reconstruction. Material and Methods: Patients were prospectively enrolled to our institution for pelvis magnetic resonance imaging because of a suspicion of endometriosis over a 4-month period. Both conventional 2D-T2 (sagittal, axial, coronal T2 oblique to the cervix) and 3D-T2-TSE sequences were performed with a scan time of 7 minutes 43 seconds and 4 minutes 58 seconds, respectively. Reconstructions with prototype ID (3D-T2-denoised) and without prototype ID (3D-T2) were generated inline at the end of the acquisition. Two radiologists independently evaluated the image quality of 3D-T2, 3D-T2-denoised, and 2D-T2 sequences. Diagnosis confidence of DIE was evaluated for both 3D-T2-denoised and 2D-T2 sequences. Intraobserver and interobserver agreements were calculated using Cohen κ coefficient. Results: Ninety female patients were included. Both readers found that the ID algorithm significantly improved the image quality and decreased the artifacts of 3D-T2-denoised compared with 3D-T2 sequences ( P < 0.001). A significant image quality improvement was found by 1 radiologist for 3D-T2-denoised compared with 2D-T2 sequences ( P = 0.002), whereas the other reader evidenced no significant difference. The interobserver agreement of 3D-T2-denoised and 2D-T2 sequences was 0.84 (0.73–0.95) and 0.78 (0.65–0.9), respectively, for the diagnosis of DIE. Intraobserver agreement for readers 1 and 2 was 0.86 (0.79–1) and 0.83 (0.76–1), respectively. For all localization of DIE, interobserver and intraobserver agreements were either almost perfect or substantial for both 3D-T2-denoised and 2D-T2 sequences. Conclusions: Three-dimensional T2-denoised imaging is a promising tool to replace conventional 2D-T2 sequences, offering a significant scan time reduction without compromising image quality or diagnosis information for the assessment of DIE.